Tamiḻttūtu Tavattiru Taṉināyaka Aṭikaḷār māṭci nayappu malar, 18-07-81 (Yāḻ. Maṟaimāvaṭṭa Kattōlikka Āciriya r Caṅkam, 1981)
Commemoration volume for Xavier S. Thaninayagam, 1913-1980, Tamil litterateur from Sri Lanka; comprises contributed articles on his life and work.